ADVANTAGES AND DISADVANTAGES OF USING METFORMIN IN AGING RELATED DISEASES - Muhammad Tola, Sakura; MH Faradz, Sultana; Handoyo Utomo, Ahmad Rusdan; Mustofa, Samsul (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
This review aimed to explore the anti-aging effects of metformin, which lowers glucose, slows down cell aging through regulating intracellular signaling molecules and activating AMPK, and protects against aging-related diseases. The activation of AMPK by Metformin allows it to control inflammatory conditions, improve oxidative status, regulate differentiation pathways of various cells, and ultimately provide positive therapeutic effects on these cells. Metformin plays a role in several cardiovascular diseases, neurological disorders, cancer, and fragile X syndrome by improving several parameters in some of these disease conditions. Metformin provides benefits in aging-related diseases, but further studies with various methods and samples are needed to assess the effectiveness and consider the side effects of metformin in diabetic and non-diabetic patients, as well as involving genetic factors associated with metformin.